2014
DOI: 10.3390/md12031406
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Potential of Monogalactosyl Diacylglycerols and a Monoacylglycerol from the Edible Brown Seaweed Fucus spiralis Linnaeus

Abstract: A monoacylglycerol (1) and a 1:1 mixture of two monogalactosyl diacylglycerols (MGDGs) (2 and 3) were isolated from the brown seaweed Fucus spiralis Linnaeus. The structures were elucidated by spectroscopic means (NMR and MS) and by comparison with the literature. Compound 1 was composed of a glycerol moiety linked to oleic acid (C18:1 Ω9). Compounds 2 and 3 contained a glycerol moiety linked to a galactose unit and eicosapentaenoic acid (C20:5 Ω3) combined with octadecatetraenoic acid (C18:4 Ω3) or linolenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 29 publications
3
47
0
Order By: Relevance
“…Furthermore, we found other two compounds claasified into diacylglycerols (1,2‐dioleylglycerol, and 1,3‐dioleylglycerol) from M. ciliatum . These compounds, which exist in several vegetable and seed oil, are well known for their functional roles in medicinal fields (AlAttas, Zahran, & Turkistany, ; Huang, Altimova, Myers, & Ebersole, ; Lopes, Daletos, Proksch, Andrade, & Valentão, ). However, and to the best of our knowledge, these compounds are very rare in higher plants.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found other two compounds claasified into diacylglycerols (1,2‐dioleylglycerol, and 1,3‐dioleylglycerol) from M. ciliatum . These compounds, which exist in several vegetable and seed oil, are well known for their functional roles in medicinal fields (AlAttas, Zahran, & Turkistany, ; Huang, Altimova, Myers, & Ebersole, ; Lopes, Daletos, Proksch, Andrade, & Valentão, ). However, and to the best of our knowledge, these compounds are very rare in higher plants.…”
Section: Discussionmentioning
confidence: 99%
“…4 u-3-PUFA act by decreasing the production of inammatory eicosanoids, cytokines and nitric oxide. 36 The monogalactosyl diacylglycerols containing u-3 fatty acids in their structure were more effective than the monoacylglycerol containing oleic acid, a u-9 fatty acid. 35 The Aplysia extracts studied herein contained signicant amounts of these three u-3 fatty acids (203.17 and 288.30 mg kg À1 , dry weight, in A. fasciata and A. punctata, respectively, Table 1), which should contribute to the overall effects.…”
Section: Cellular Viabilitymentioning
confidence: 97%
“…Concerning to the last, it has been previously shown that the expression of iNOS was inhibited by EPA, DHA 33 and also a-linolenic acid. 36 So, u-3 fatty acids, not only in the free form, but also in complex molecules, appear to contribute most to the anti-inammatory activity. The presence of higher amounts of u-3 fatty acids in A. punctata is accompanied by the presence of higher amounts of the pro-inammatory fatty acid cis-5,8,11,14-eicosatetraenoic (arachidonic acid) and the balance between the compounds can impart similar effects on cNO of A. punctata and A. fasciata extracts.…”
Section: Cellular Viabilitymentioning
confidence: 99%
“…Some studies reported that polar lipids isolated from seaweeds can promote growth-inhibiting effects on human hepatocellular carcinoma cell lines (HepG2) [16] and thus can act as inhibitors of DNA polymerases with capability to inhibit tumor cell proliferation [17]. Moreover, they have been associated with anti-inflammatory properties through the inhibition of pro-inflammatory cytokines interleukin IL-6 and IL-8 production [15] and/or by the inhibition of nitric oxide (NO) production [18,19,20,21]. Lipid-based agents are therefore emerging molecules in therapeutics aimed to regulate inflammatory pathways or even impair downstream tumorigenic processes [22,23,24].…”
Section: Introductionmentioning
confidence: 99%